Towards augmented connectivity with delay constraints in WSN federation. (14th November 2012) - Al–Turjman, Fadi M.; Hassanein, Hossam S.
Inconsiderate WSN federation can impose a major network delay. In this paper, we look into the problem of WSN federation while considering a restricted delay between the federated segments. Towards this end, we propose two schemes for relay node placement in federating WSNs: Connectivity–Based Placement (CBP) and Connectivity–Based Placement with Delay–constraint (CBP–D). CBP maximises the connectivity of the network without any delay considerations, while CBP–D maximises the network connectivity with an upper bound on the maximum delay. We model the disjoint segments of the network to be federated into graph vertices and populate first phase relays to establish a connected graph. Consequently, second phase relays are populated to maximise the graph connectivity while maintaining cost (in CBP) and delay constraints (in CBP–D). Simulation results show that our schemes maximise the network connectivity significantly as compared to existing placement schemes in WSN federation, in addition to guaranteeing a very limited delay.